Clinical Efficiency of Non-invasive Prenatal Screening for Common Trisomies in Low-Risk and Twin Pregnancies - Xu, Yanfei; Jin, Pengzhen; Lei, Yu; Qian, Yeqing; Xu, Yuqing; Wang, Miaomiao; Jin, Jinglei; Yin, Yixuan; Dong, Minyue (Frontiers in Genetics, 2021)
In this study, we aimed to evaluate the clinical efficiency of noninvasive prenatal screening (NIPS) for common trisomies in low-risk and twin pregnancies. Patients who received NIPS in a tertiary university hospital were enrolled. Clinical data of patients, NIPS results, and pregnancy outcomes were collected from 2015 to 2019. Patients were divided into singleton and twin pregnancies, and then were divided into low-risk and high-risk pregnancies in singleton populations. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of NIPS were estimated in the overall population and each group. Comparisons of singleton and twin pregnancies, as well as low- and high-risk pregnancies were made on the clinical efficiency of NIPS. Of 66,172 enrolled patients, 59,962 were eligible for analysis. The sensitivity, specificity, and NPV were ≥99% in singleton and twin pregnancies. The PPVs were 90.4% (95% confidence interval [CI] 85.8-93.9), 56.6% (95% CI 45.3-67.5), and 13.0% (95% CI 4.9-26.3) in singleton pregnancies, as compared with 100% (95% CI 59.0-100), 33.3% (95% CI 0.8-90.6), and 0% (95% CI 0-52.2) in twin pregnancies for trisomy 21, 18, and 13, respectively (for paired groups, P>0.05). The PPVs were 97.4% (95% CI 86.5-99.9) and 90.0% (95% CI 55.5-99.7) in high-risk pregnancies, as compared with 78.6% (95% CI 59.0-91.7) and 16.7% (95% CI 3.6-41.4) in low-risk pregnancies of standard screening for trisomy 21 and 18, respectively (for paired groups, P<0.05). Two false negative trisomy 21 were identified in pregnancies with abnormal ultrasonography. In summary, the performance of NIPS in singleton pregnancies was similar to that in twin pregnancies. NIPS can be recommended for pregnancies with all risk levels, but fetuses with abnormal ultrasonography should undergo prenatal diagnosis. Fetal mosaicism is an important cause of false negative NIPS result, and confined placental mosaicism is a possible cause of false negative NIPS result.